OPTIMALISASI PERAN DINAS KOPERASI DALAM SISTEM PROGRAM PENGAWASAN PADA KOPERASI KARYAWAN BANK MEGA - Dwiki Darmawan, Septian; Kustini, Kustini (Gapenas Publisher, 2024)
The objective of this community service is to examine how the role of the Cooperative Department can be optimized to enhance the sustainability of operations at the Bank Mega Employee Cooperative through cooperative supervision mechanisms. Comprehensive interviews were conducted with the cooperative's management, members, and staff, supplemented by observations. The results indicate that transparency and accountability in cooperative management are significantly influenced by the supervision carried out by the cooperative organization. The cooperative management team receives regular training and evaluations through supervision programs, which not only help identify managerial issues but also enhance member participation in decision-making processes. Effective supervision also enables the organization to maintain sustainable operations by aligning its strategies and activities with changes in the business environment. This study concludes that optimizing the role of the Cooperative Department through systematic and well-planned supervision can improve the performance of the Bank Mega Employee Cooperative, thereby providing greater benefits to its members. To ensure that cooperatives can address existing challenges and achievetheir long-term objectives, it is recommended to strengthen supervision and develop more comprehensive training programs for the management team.